Dependence of Seebeck Coefficient on the Density of States in Organic Semiconductors - Shi, Xiaohong; Sun, Jiuxun (IEEE electron device letters, 2017)
The thermoelectric properties of organic semiconductors are studied theoretically. Based on the Miller-Abrahams hopping model and the concept of genuine transport energy, we obtained the analytic expressions of carriers concentration, conductivity, and Seebeck coefficient. Combining an exponential-type density of states with clear cutting tail at some places, the dependence of Seebeck coefficient on carrier concentration and temperature can be evaluated. The numerical results with optimized parameters describe the experimental data well.